2015
DOI: 10.3892/ol.2015.3197
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent 12q13-15 chromosomal aberrations, high frequency of isocitrate dehydrogenase 1 mutations, and absence of high mobility group AT-hook 2 expression in periosteal chondromas

Abstract: Abstract. Periosteal chondroma is a benign cartilage tumor that accounts for <2% of chondromas. In the present study, four cases of periosteal chondromas were cytogenetically investigated and studied for the expression of high-mobility group AT-hook 2 (HMGA2), mutations in codons 132 of isocitrate dehydrogenase (IDH)1 and 172 of IDH2; mutations -C228T and -C250T in the promoter region of telomerase reverse transcriptase (TERT); and for methylation in the promoter regions of O-6-methylguanine-DNA methyltransfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Mutation-positive central and periosteal cartilaginous tumors occurred more frequently in the tubular bones of the hands and feet than at other anatomical 90% of the acral-based tumors revealed a mutation, compared to 53.2% of tumors in the long bones of the appendicular skeleton, and 35.1% of those in the flat bones [10]. Other study also support the finding of IDH-1 mutation in periosteal chondromas [11]. When we re-viewed the literature it has been seen that this mutation status does not have any effect on prognosis.…”
Section: Discussionsupporting
confidence: 61%
“…Mutation-positive central and periosteal cartilaginous tumors occurred more frequently in the tubular bones of the hands and feet than at other anatomical 90% of the acral-based tumors revealed a mutation, compared to 53.2% of tumors in the long bones of the appendicular skeleton, and 35.1% of those in the flat bones [10]. Other study also support the finding of IDH-1 mutation in periosteal chondromas [11]. When we re-viewed the literature it has been seen that this mutation status does not have any effect on prognosis.…”
Section: Discussionsupporting
confidence: 61%
“…Expression of HMGA2 was found in both examined skeletal chondromas: a tumor with a pericentric inv( 12 )(p12q13) expressed a truncated transcript of HMGA2 whereas a tumor carrying a t(2;11)(q37;q13) without visible involvement of 12q expressed the full length HMGA2 transcript ( 38 ). On the other hand, neither conventional RT-PCR nor real-time PCR showed expression of HMGA2 in the examined periosteal chondromas, although two of them had structural aberrations of chromosome bands 12q13~15 ( 39 ).…”
Section: Discussionmentioning
confidence: 74%
“…It should be emphasized that the role of HMGA2 in chondromatous tumors is still studied only very rudimentary in-as-much as only six soft tissue chondromas, two skeletal chondromas, and three periosteal chondromas have been subjected to this type of analysis ( 38 , 39 ). HMGA2 expression was found in four soft tissue chondromas of which three expressed a truncated transcript of HMGA2 and one the full length transcript 1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cytogenetic studies of PC have shown a loss of chromosome 6 and rearrangements of 2q37, 4q21-25, and 11q13-15 [ 14 ]. Panagopoulos et al also reported chromosome aberrations of 12q13-15 in two of their four cases [ 12 ]. In existing literature, there has been no association shown between PC and other tumors or family history of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of PC is poorly understood. However, similar to enchondroma, PC frequently harbors heterozygous mutations in isocitrate dehydrogenase (IDH) genes mostly involving IDH1 mutation at R132 [11][12][13]. In addition, cytogenetic studies of PC have shown a loss of chromosome 6 and rearrangements of 2q37, 4q21-25, and 11q13-15 [14].…”
Section: Discussionmentioning
confidence: 99%